Exchange Rate Volatility and Export Growth: Post-Reform Experience of India - Bhanja, Niyati; Samantaraya, Amaresh; Dar, Arif Billah (Indian Journal of Finance, 2013)
This paper seeks to investigate empirically the impact of exchange rate volatility on India's export growth over the period between from April 1993 to September 2010. The measure of volatility is estimated for both the nominal and the real effective exchange rate (NEER and REER) using Bollerslev's GARCH model and the wavelet decomposition technique. The ordinary least square (OLS) procedure is then employed to verify the link between export growth and the volatility of exchange rate. The results of ordinary least squares (OLS) suggests that both real and nominal exchange rate volatility exerts a significant positive impact on export growth, irrespective of different measures of volatility employed. Moreover, corroborating conventional wisdom, the foreign economic activities and the domestic import are also found to have a significant positive effect on the growth of exports.